2013
DOI: 10.5812/hepatmon.11781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR-RFLP in the Pre-S Region as Molecular Method for Hepatitis B Virus Genotyping

Abstract: BackgroundHepatitis B virus (HBV) infection is a public health problem in developing countries. HBV genotypes play major role in the evolution of infection since they were involved in different clinical presentations and response to treatment.ObjectivesThis study was conducted to evaluate the efficiency of restriction fragment length polymorphism (RFLP) analysis for HBV genotyping.Patients and MethodsWe investigated 98 samples collected from patients chronically infected with HBV. HBV genotypes were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Genotyping showed that genotype D was detected in the 5 studied patients. This genotype was previously described as a predominant HBV genotype in Tunisia and the Maghreb region as well as in the Middle East with a low co-circulation rate of genotype E (Ayed et al, 2007;Ezzikouri et al, 2008;Ouneissa et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…Genotyping showed that genotype D was detected in the 5 studied patients. This genotype was previously described as a predominant HBV genotype in Tunisia and the Maghreb region as well as in the Middle East with a low co-circulation rate of genotype E (Ayed et al, 2007;Ezzikouri et al, 2008;Ouneissa et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…It is important to take into account the genetic variability of HBV when identifying the polymorphisms that modify RFLP patterns present at each restriction enzyme recognition site. Nevertheless, RFLP continues to be used for HBV genotyping (32,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Various RFLP protocols for HBV genotyping have been described, most of them based on the amplification and restriction of ORF S sequences (23,(27)(28)(29). The RFLP method is used in genotyping studies because it is a simple and relatively inexpensive method to determine the HBV genotype, particularly for large-scale analyses (30)(31)(32).…”
mentioning
confidence: 99%
“…In Eastern Europe and Mediterranean countries, the most prevalent is genotype D (6). According to literature reports, along with genotype C, genotype D produces a more aggressive course of the disease and brings lower response rates to antiviral therapy (7)(8)(9)(10). Literature focused on this issue explains that mutations in the S gene could lead to structural and functional alter-ations in the HBV reverse transcriptase, with potential influence on viral replication capacity and efficacy of antiviral drugs, the escape mutants eluding the immune system, and explaining the coexistence of HBsAg and anti -HBsAb (11,12).…”
Section: Introductionmentioning
confidence: 99%